Spatiotemporal Characteristics and Trend Analysis of Soil Moisture and Its Memory Effect in the Minjiang River Basin - YIN Fangxu; YOU Jiewen; ZHANG Yinchi; WU Jingwen; GAO Lu (Renmin Zhujiang, 2025)
This study investigated the spatiotemporal differentiation characteristics of soil moisture and its memory effect in the Minjiang River Basin, aiming to provide a scientific basis for water resources management, as well as flood prevention and disaster reduction in humid regions. Based on a 1 km grid daily-scale soil moisture dataset (2000—2022), regression fitting and autocorrelation coefficient methods were applied to systematically analyze the spatial gradient, interannual variation, seasonal dynamics, and memory effects of soil moisture in the basin. Soil moisture in the Minjiang River Basin exhibits a significant northwest-southeast decreasing trend, with high-value zones (>0.43 m3/m3) concentrated in the Wuyi Mountain Forest Ecological Zone and low-value zones (<0.39 m3/m3) distributed along the coastal urbanized plains. Seasonal dynamics reveal a spring peak (0.44 m3/m3) and a decline to 0.39 m3/m3 in autumn. The memory effects of soil moisture at different depths show spatial differentiation characteristics, and the memory time of deep soil in the lower reaches of the Minjiang River is lower than 30 days. The soil moisture in the Minjiang River Basin shows spatiotemporal differentiation. The memory effects demonstrate depth-space heterogeneity, reflecting the synergistic regulatory effects of factors such as precipitation, temperature, and vegetation coverage. The findings enhance the understanding of soil moisture and provide implications for flood warning and water resource management in the Minjiang River Basin.